2014
DOI: 10.5137/1019-5149.jtn.9376-13.1
|View full text |Cite
|
Sign up to set email alerts
|

Empty bladed peek cage for interbody fusion after acd

Abstract: ABSTRACTassociated with uncontrolled fusion and cervical kyphosis, particularly in cases with 2 and 3 level CDH (30).On the other hand, the addition of a disc prosthesis after ACD has some theoretical advantages, including motion preservation, and reduced rate of adjacent segment disease. However, adjacent segment problem, heterotopic ossification and high cost related problems remain (45, 50).another technique, anterior cervical foraminotomy, is an effective technique, particularly for foraminal herniations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
(20 reference statements)
1
5
0
3
Order By: Relevance
“…Therefore, the achieved mechanical decompression of the compressed cervical roots and the possible restoration of the local micro-circulation may result in pain reduction [ 13 ]. Consistent with other clinical series [ 4 , 10 , 11 , 14 - 16 ], our current data clearly indicated that there was a statistically significant reduction of neck/arm pain among our patients at their discharge from the hospital. This effect was maintained during their 12-month follow-up period.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, the achieved mechanical decompression of the compressed cervical roots and the possible restoration of the local micro-circulation may result in pain reduction [ 13 ]. Consistent with other clinical series [ 4 , 10 , 11 , 14 - 16 ], our current data clearly indicated that there was a statistically significant reduction of neck/arm pain among our patients at their discharge from the hospital. This effect was maintained during their 12-month follow-up period.…”
Section: Discussionsupporting
confidence: 92%
“…The essential purpose of ACDF with a PEEK cage is to decompress the spinal cord and other neural structures whilst to maintain the stability of the cervical spine. Additionally, there is strong body of evidence that PEEK cage implantation restores and successfully maintains the intervertebral disc height and also the neural foramina height, postoperatively [ 4 , 10 - 12 ]. Therefore, the achieved mechanical decompression of the compressed cervical roots and the possible restoration of the local micro-circulation may result in pain reduction [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cho et al [14] utilized radiographs to assess fusion without any further details on how fusion was objectively measured. Three studies determined fusion through evaluating motion on lateral cervical radiographs and bone bridging on computed tomography (CT) scan [20,23,30]. Zhou et al [15], Liao et al [16], and Klingler et al [19] evaluated fusion by using CT scans only.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [15], Liao et al [16], and Klingler et al [19] evaluated fusion by using CT scans only. The subsidence rate was evaluated vaguely by radiographs in three studies [14,16,23]. Three studies defined subsidence as the radiographic change of at least 3 mm in the interbody space [13,17,24,25], whereas another two studies considered subsidence as a change of at least 2 mm in the interbody distance [21,22].…”
Section: Introductionmentioning
confidence: 99%